A Force Field Simulation Approach to Analyze the Molecular Structure Stability of Cyanidin-3-Glucoside Using Avogadro: A Preliminary Study - Putro, Permono Adi; Wulandari, Desi; Wulandari, Devia Putri; Nurfaidah, Fitriah; Ahdan, M Farid; Chaerunnisa, Seviana; Octaviani, Vina Umaya (Universitas Mandiri, 2024)
Cyanidin-3-glucoside (C3G) is a flavonoid compound that is an antioxidant and natural colorant widely found in berries and vegetables such as red cabbage. This study aims to explore the structural stability of C3G using computer simulations based on force field theory through Avogadro software. In this study, the Universal Force Field (UFF), Merck Molecular Force Field (MMFF94), and General Amber Force Field (GAFF) methods were used to analyze the stability of C3G. The energy optimization results showed that the Ghemical method produced a more stable structure than other methods, although there was a discrepancy with GAFF. The GAFF method was more stable than UFF, but required more energy to achieve stability. Overall, the difference in force field methods affected the molecule's stability through optimization energy and structure parameterization variations, which affected the distance and angle of atomic bonds. These findings provide an efficient picture of the stable conformation of C3G, which can be applied in the food, health, and cosmetic industries.